RANCANGAN EVALUASI PROGRAM KKNP SANTO BONAVENTURA DENGAN MODEL CIPP - Simbolon, Erikson (IN VERITATE LUX, 2018)
The purpose of writing this article is to find out how to design an evaluation of a context, input, process, product (CIPP) education program, the purpose and function of a context, input, process, product (CIPP) program evaluation, and the steps for evaluating a context, input, process program, product (CIPP). The evaluation was carried out on the real pastoral work study program currently being implemented. This evaluation should be carried out by an external evaluator to maintain the independence of the evaluation results. The evaluation results can be used as input as to whether the program implemented is good or not based on the competencies that will be mastered by the student. If it is good then the program can be continued and if not then it is stopped based on input from the program evaluation maker